Microcystin MC-LR in Brazilian aquaculture production systems - Barros, Ludmilla S. S.; Tavares, Lúcia Helena S. [UNESP]; Amaral, Luiz A. [UNESP] (My University, 2011)
The growth of aquaculture production systems, mostly the sports-fishing kind, coupled to lack of control, brings about concerns on the quality of water and food produced. Current paper determines which factors may trigger the growth of cyanobacteria with subsequent concentrations of microcystins in collected water samples, at the surface and in the water column, from ten aquaculture systems, during the dry and rainy seasons. The above is undertaken by measurements of biotic (counting of Chlorophyceae, cyanobacteria and MC-LR) and abiotic (total nitrogen and total phosphorus) factors. Since water of ten aquaculture production systems had MC-LR concentrations highly correlated with M. aeruginosa biomass, most MC-LR microcystins were produced by this species. MC-LR concentrations and M. aeruginosa counting were positively correlated with N:P rates and suggest that parameters may affect not only the M. aeruginosa biomass but also MC-LR concentrations. © 2010 Nova Science Publishers, Inc.
Keywords: Cyanobacteria; Eutrophication; Hplc; Nitrogen; Phosphorus